2021
DOI: 10.1530/eje-20-1481
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of active surveillance of EU-TIRADS 5 thyroid nodules

Abstract: Objective: Active surveillance of cytologically proven microcarcinomas has been shown as a safe procedure. However, fine needle aspiration biopsy (FNAB) is not recommended by European Thyroid Association (ETA) and American Thyroid Association (ATA) guidelines for highly suspicious nodules ≤ 10mm. The aim of the study was to assess the outcomes of active surveillance of EU-TIRADS 5 nodules ≤ 10 mm not initially submitted to FNAB. Patients and Methods: 80 patients with at least one EU-TIRADS 5 nodule ≤ 10 mm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We simulated an ideal monitoring environment with the physician providing intensive reminders for AS and follow-up to evaluate patient adherence with an ideal AS healthcare team. Ultimately, there was satisfactory overall adherence in our cohort, and only 5.2% of patients were considered to have poor adherence (loss to follow-up or noncompliance), which was better than that in Italy (10.8%) (18), similar to that in France (6.3%) (25) and much lower than that in the United States (0.7%) (22). However, although patients were given both oral and written instructions at every visit to return for surveillance, many patients still did not return for AS until a manual reminder was sent by the follow-up doctor.…”
Section: Patient Adherencementioning
confidence: 59%
“…We simulated an ideal monitoring environment with the physician providing intensive reminders for AS and follow-up to evaluate patient adherence with an ideal AS healthcare team. Ultimately, there was satisfactory overall adherence in our cohort, and only 5.2% of patients were considered to have poor adherence (loss to follow-up or noncompliance), which was better than that in Italy (10.8%) (18), similar to that in France (6.3%) (25) and much lower than that in the United States (0.7%) (22). However, although patients were given both oral and written instructions at every visit to return for surveillance, many patients still did not return for AS until a manual reminder was sent by the follow-up doctor.…”
Section: Patient Adherencementioning
confidence: 59%
“…After full text review, 14 studies were included for the final analysis. The results are summarized in the PRISMA flowchart (Figure 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…After full text review, 14 studies were included for the final analysis. The results are summarized in the PRISMA flowchart (Figure 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The authors used the Newcastle-Ottawa Scale (NOS) to certify the quality of each included study.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that proceeding to AS without FNAB is a safe procedure in selected patients, and FNAB could be postponed until disease progression 83 . An increased frequency of ultrasound re-examination may be more acceptable to Chinese patients than invasive procedures, because it is inexpensive and convenient.…”
Section: Enhancing Adherence During the Follow-upmentioning
confidence: 99%